PROGRAM AKSELERASI PADA PERGURUAN AL-AZHAR MEDAN: Implementation of the Al-Azhar Medan College Acceleration Program - anggraini, Astrie; Fatimah, Tri (Yayasan Pendidikan Islam Akmalia, 2021)
The State of Indonesia is one of the countries that has development and coaching programs of all levels and types, both informal, formal, and non-formal education. The implementation of acceleration for students who have extraordinary abilities and intelligence, is one of the relevant alternatives, because students who have extraordinary abilities and intelligence have learning speed and learning motivation above the speed and motivation of learning other students. This alternative strategy in addition to aiming to provide educational services according to the potential of students. The implementation of CBSA learning programs, superior learning programs (classes), accelerated learning programs (classes), international standard school programs (SBI) and the change of the 1994 curriculum to the 2004 curriculum, the 2004 curriculum to the KTSP curriculum are some examples of government efforts. This article discusses the process of implementing the acceleration program at Al-Azhar University Medan. Where in the acceleration program of Al-Azhar College Medan there are activities implemented for students who have extraordinary abilities and intelligence, by being given the opportunity to be able to complete studies in elementary schools for less than 6 years (for example 5 years), in junior high and high schools of less than 3 years each (for example 2 years), by completing all curriculum targets without jumping classes.